2007
DOI: 10.1103/revmodphys.79.929
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium: Illuminating the Kapitza-Dirac effect with electron matter optics

Abstract: The observation of the Kapitza-Dirac effect raises conceptual, theoretical, and experimental questions. The Kapitza-Dirac effect is often described as diffraction of free electrons from a standing wave of light or stimulated Compton scattering. However, for the two-color Kapitza-Dirac effect these two interpretations appear to lead to paradoxical conclusions. The discussion of this paradox deepens our understanding of both of these versions of the Kapitza-Dirac effect. DOI: 10.1103/RevModPhys.79.929 PACS numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 45 publications
5
137
0
Order By: Relevance
“…Related experiments studied KD scattering on atomic beams [21]. For reviews on the subject, we refer to [22,23]. Moreover, recent studies on spininsensitive KD scattering may be found in [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Related experiments studied KD scattering on atomic beams [21]. For reviews on the subject, we refer to [22,23]. Moreover, recent studies on spininsensitive KD scattering may be found in [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…As already noted, the pulsed mode technology is already successfully employed for high resolution pump-probe electron microscopy and has produced the photon-induced electron energy loss and gain events discussed above. Equation (4) indicates that in these experiments the ponderomotive potential must also give rise to a phase shift φ = e 2 E p / 16π. The 400 fs interaction time indicated in [7] for the photon and electron pulses would correspond for a 200 keV electron to a propagation distance L of 80 μm in the illumination field E i with peak radiance cε 0 E i 2 /4 of 10 15 Wm -2 .…”
Section: Discussion Of Future Prospectsmentioning
confidence: 99%
“…For propagation parallel to the optical nodes and antinodes however equation (4) shows that the phase shift will vary periodically with x, resulting in undesirable oscillations between phase and amplitude contrast across the diffraction plane. This effect would be mitigated for propagation across the curved wave fronts in a spherical or parabolic cavity but, for propagation through less sharply focused standing wave systems, it would be better for the fast electron to travel cross the antinodes at an angle chosen to sample them evenly (as for direction e2 in fig 1).…”
Section: Ponderomotive Refraction and Kapitza-dirac Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The near field of the surface charge may mimic the pattern of the light, and electron matter waves could be coherently controlled in this manner analogous to the Kapitza-Dirac effect or temporal lensing [11,12], but without the need for high laser intensity. Finally, we speculate that the combination of laser pulses and nano-fabricated structures will make femtosecond manipulation of free electrons accessible at low intensities [7,13,14].…”
mentioning
confidence: 99%